Perception and Use of Social Media as News Sources by Undergraduate Students of Caleb and Leadcity Universities - Akande, Emme; Falobi, Funmi; Akin-Odukoya, Omolara Oluwabusayo; Ajasa, Omobolarinwa; Ridwan, Muhammad (BIRCU, 2024)
Social media enable users to engage with others and present themselves selectively to a wide or specific audience. These platforms enable real-time interaction and content creation, which are valued by users. Social media has significantly impacted how people socialise and connect on a global scale, bringing about significant changes in social dynamics. This study examines the perception and use of social media as news sources by undergraduate students of Caleb and Leadcity universities students. The research has the following objectives: to examine patterns of mass communication undergraduates’ use social media, to identify what factors motivate mass communication undergraduates to use social media and to determine the perceptions of mass communication undergraduates about social media. The research made use of Media Richness Theory. The purposive sampling method was used for this study. The population of the study consisted of all mass communication undergraduate students of Caleb University and Leadcity University and 400 questionnaires were distributed to the respondents. The study discovered that a large number of people make-use of social media regularly and spend nothing less than an hour every-day. The study also discovered that most students use social media for timely updated information, they use it to communicate regularly. Equally, the students also used it for alternative view points on an issue.